Status Hama Brontispa longissima (Gestro) pada Pertanaman Kelapa di Kabupaten Biak Numfor, Provinsi Papua - JELFINA C. ALOUW; DIANA NOVIANTI (Buletin Palma, 2010)
Status of Brontispa longissima (Gestro) Pest on Coconut Plantationin Biak Numfor District, Papua ProvinsiB. longissima (Coleoptera : Chrysomelidae) originated from Aru Island and Papua has damaged and caused loss of coconut production in Indonesia and Asia Pasific regions. A research to generate information on the status of this pest such as pest and natural enemies population and damage level was conducted in June 2010 in Biak District, Papua Province. A total of nine villages of three sub districts in Biak District, Papua Province were surveyed and Brontispa-attacked coconut palms were purposively observed. Damage level was assesed from four fully opened young coconut leaflets. Damage level in Samofa Subdistrict (42,63%) and East Biak (33,73) was higher than that in North Biak (22.12%). It was relating with the pest population per palm in each district where the highest pest population was found in Samofa sub district, followed by East Biak and the lowest in North Biak. Reduction of coconut production wasestimated to 40 – 60%. Two natural enemies identified were (Hymenoptera: Eulophidae) and predator earwig (Dermaptera).